Forkhead box protein C2 contributes to invasion and metastasis of extrahepatic cholangiocarcinoma, resulting in a poor prognosis. Issue 11 (15th September 2013) - Watanabe, Akira; Suzuki, Hideki; Yokobori, Takehiko; Altan, Bolag; Kubo, Norio; Araki, Kenichiro; Wada, Satoshi; Mochida, Yasushi; Sasaki, Shigeru; Kashiwabara, Kenji; Hosouchi, Yasuo; Kuwano, Hiroyuki
Abstract : Extrahepatic cholangiocarcinoma (EHCC) is a cancer with a poor prognosis, and the postoperative survival of patients depends on the existence of invasion and metastasis. The epithelial‐to‐mesenchymal transition (EMT) is an important step in EHCC invasion and metastasis. Forkhead box protein C2 ( FOXC2 ) is a transcription factor that has been reported to induce the EMT. Therefore we examined the correlation between FOXC2 expression and clinical pathological factors, and analysed the function of FOXC2. The expression of FOXC2 in 77 EHCC cases was investigated by immunohistochemical staining, and the relationship between FOXC2 expression and clinicopathological factor was assessed. Knockdown by small interfering RNA (siRNA) was performed to determine the roles of FOXC2 in EHCC cell line. FOXC2 expression correlated with lymph node metastasis ( P = 0.0205). Patients in the high FOXC2 expression group had a poorer prognosis than the patients in the low FOXC2 expression group. Moreover, FOXC2 knockdown inhibited cell motility and invasion, and decreased the expression of EMT markers (N‐cadherin, and matrix metalloproteinase (MMP) ‐2) and Angiopietin‐2 (Ang‐2). The EMT inducer FOXC2 contributes to a poor prognosis and cancer progression. FOXC2 may be a promising molecular target for regulating EHCC metastasis.